Correlation of carbon doping variations with the vertical breakdown of GaN-on-Si for power electronics. (November 2016) - Knetzger, Michael; Meissner, Elke; Derluyn, Joff; Germain, Marianne; Friedrich, Jochen
Abstract: In this work gallium nitride (GaN) grown on silicon substrates was investigated in order to determine critical defects responsible for differences in the vertical breakdown of HEMT structures. Cathodoluminescence studies at the SEM revealed a direct correlation between the intensity of the blue luminescence (BL) band and the carbon doping concentration. Observing this, carbon depletion zones were found around threading dislocations in the active GaN layer, as well as a deep depletion in growth columns concluded from a reduction of the BL intensity. Using the given results a model of a defect, here called the deep carbon depletion (DCD), is proposed to explain the correlation between carbon variations and the vertical breakdown. Highlights: Microstructural investigations of GaN-on-Si for power electronics Correlation of local carbon distribution a vertical breakdown Defect found responsible for decreased breakdown strength